Analysis of the tools and materials used in tailoring, embroidering and weaving the Bisht, the stages of embroidering the Bisht, its names and colours - Alzahrani, Khyrah Awad Awadh (Journal of Humanities & Social Sciences, 2023)
The aim of the research is to identify the tools and materials used in the tailoring, embroidery, and weaving of the traditional Saudi garment known as "Bisht." It also aims to explore the stages of Bisht embroidery, its names, colors, and to understand the historical origins associated with Bisht as a national and traditional attire for Saudi men. Furthermore, the research seeks to highlight the distinctive characteristics of Bisht in Saudi Arabia. The researcher adopted a descriptive survey methodology, which involves finding facts and collecting qualitative data directly from a study sample consisting of four embroiderers working in the craft of Bisht manufacturing, in addition to one of the owners of Bisht manufacturing companies. Data was collected through a questionnaire based on the study’s objectives, and the collected data was analysed using direct narrative analysis. The research arrived at several conclusions, including that the history of Bisht manufacturing and weaving in Al-Ahsa dates back to the period after the emergence of Islam, as suggested by some researchers. This was confirmed by the craftsmen who have inherited this craft from generation to generation. Bisht is made from various materials, including camel and goat hair. The wool is spun and undergoes a specific time period before being transformed into fabric ready for use in Bisht manufacturing. Other materials such as cotton are also used, and the names of the materials vary, including Najafi, Japanese, German, and Indian fabrics. Regarding the materials used, their thickness varies according to the seasons. Summer Bishts are characterised by their lightweight and thinness, while winter Bishts are thicker and heavier, filled with wool and fur for more warmth. Bishts are manufactured for three seasons, including summer, winter, and a moderate thickness for spring or autumn. The manufacturing process of Bisht goes through many stages including the foundation stage, the "Hila" stage, the Upper side installation, the "Buruj" stage, and the "Maksar" stage.